Business tourism in an African city: Evidence from Harare, Zimbabwe - Logistic Makoni; Christian M. Rogerson (Studia Periegetica)
Research on business tourism is attracting greater interest from tourism scholars in the Global North. Scholarship on business tourism in the Global South, however, remains underdeveloped despite its significance for many leading urban tourism destinations. Arguably, the need for the growth of research on business tourism is particularly acute in major cities of sub-Saharan Africa where the sector is frequently of more significance than leisure tourism. This article contributes to addressing the knowledge gap on business tourism in urban Africa with its focus on MICE tourism in Harare, Zimbabwe’s capital city. Use is made of a set of qualitative interviews which were conducted with stakeholder representatives for all hotels in Harare that have facilities to accommodate business events. Under scrutiny are the competitiveness of the city’s business tourism economy, the nature of business events in the city, and local pro-poor impacts.